2020
DOI: 10.1093/heapol/czaa062
|View full text |Cite
|
Sign up to set email alerts
|

What happens when performance-based financing meets free healthcare? Evidence from an interrupted time-series analysis

Abstract: In spite of the wide attention performance-based financing (PBF) has received over the past decade, no evidence is available on its impacts on quantity and mix of service provision nor on its interaction with parallel health financing interventions. Our study aimed to examine the PBF impact on quantity and mix of service provision in Burkina Faso, while accounting for the parallel introduction of a free healthcare policy. We used Health Management Information System data from 838 primary-level health facilitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 60 publications
1
12
0
Order By: Relevance
“…Unfortunately, routine data on medicine availability to test for parallel trends pre-intervention are not available. However, an interrupted time series study on the impact of PBF in Burkina Faso on various health care utilization indicators showed no difference in pre-intervention trends for the majority of investigated EM-dependent services, supporting our assumption that this was the case for EM availability as well [30].…”
Section: Plos Global Public Healthsupporting
confidence: 64%
“…Unfortunately, routine data on medicine availability to test for parallel trends pre-intervention are not available. However, an interrupted time series study on the impact of PBF in Burkina Faso on various health care utilization indicators showed no difference in pre-intervention trends for the majority of investigated EM-dependent services, supporting our assumption that this was the case for EM availability as well [30].…”
Section: Plos Global Public Healthsupporting
confidence: 64%
“…A recent study on the free healthcare policy in Burkina showed that prior to this policy, there were significant positive effects of the PBF on maternal and child service utilisation. After the introduction of the free healthcare policy, however, PBF no longer impacted service utilisation in intervention compared with control facilities [34]. Given these observed changes in service utilisation at the facility level in response to the free healthcare policy, it might be likely a similar trend pattern occurred with respect to service use at the level of households in the respective catchment areas.…”
Section: Discussionmentioning
confidence: 99%
“…To estimate the effect of PBF on the different ANC quality outcomes, we used a difference-in-differences approach based on linear regression. The assumption of parallel trends prior to intervention was con rmed using routine data from these study facilities for selected ANC indicators (41). As treatment assignment occurred at district level, we clustered standard errors at that level.…”
Section: Analytical Approachmentioning
confidence: 99%